A new method for extending the range of conductive polymer sensors for contact force - Carvalho, A. A.; Radwin, R. G. (Elsevier B.V., 1996)
This paper describes a technique for extending the force range of thin conductive polymer force sensors used for measuring contact force. These sensors are conventionally used for measuring force by changing electrical resistance when they are compressed. The new method involves measuring change in electrical resistance when the flexible sensor, which is sensitive to both compression and bending, is sandwiched between two layers of spring steel, and the structure is supported on a thin metal ring. When external force is applied, the stiffened sensor inside the spring steel is deformed within the annular center of the ring, causing the sensor to bend in proportion to the applied force. This method effectively increases the usable force range, while adding little in the way of thickness and weight. Average error for loads between 10 N and 100 N was 2.2 N (SD = 1.7) for a conventional conductive polymer sensor, and 0.9 N (SD = 0.4) using the new approach. Although this method permits measurement of greater loads with an error less than 1 N, it is limited since the modified sensor is insensitive to loads less than 5 N. These modified sensors are nevertheless useful for directly measuring normal force applied against handles and tools and other situations involving forceful manual work activities, such as grasp, push, pull, or press that could not otherwise be measured in actual work situations.
Keywords: contact force; force sensor; physical stress measurement